Meningkatkan Kualitas Pelayanan Publik Dalam Gaya Kepemimpinan Servant Leadership - Danang Nugroho; Alviana Cahara Setiadi; Daffa Anisa Putri; Fahrul Khoerul Imam; Neulis Lia Purwanti; Yulia Septihayati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Leaders use their leadership characteristics to manage and direct the organization towards achieving predetermined goals. Servant leadership is a leadership style that focuses on the virtues of serving and supporting the needs of others.This journal applies a qualitative descriptive method and adopts a literature review approach to evaluate various sources such as journals and news related to the concept of servant leadership. This study aims to assess the influence of servant leadership on improving the quality of public services.A service-oriented leadership style, or servant leadership, has an indirect relationship with improving the quality of services provided to the public. Leaders who implement servant leadership tend to increase organizational commitment among employees, which in turn can improve their performance. Organizational commitment, which leads to a desire to contribute more and remain part of the organization, can indirectly improve the quality of public services through increased employee commitment and performance. Leaders who embrace this principle seek to maximize their ability to strengthen organizational commitment.